Analisis Pemetaan Potensi Daerah Provinsi Jawa Barat Dengan Menggunakan Metode Klassen - WulandariÂ , Putri (Pusat Pembelajaran dan Strategi Kebijakan Talenta Aparatur Sipil Negara Nasional, 2014)
lncreased regional competitiveness can be done through a process of carq'ul planning. The planning process is done through an analysis can outline the potential of supporting the competitiveness of the region into the region in the implementation ofdevelopment. One technique that can be used to determine the potential ofan area is to use the method ofKlassen. With this method for mapping potential of West lava Province is concluded that the Province of West lava has an advantage in Sector Trade, Hotels and Restaurants. Sector Potential in West lava Province is Agriculture and Processing Industry Sector. Meanwhile, Growing Sector in West lava Province is Sector Electricity, Gas and Water Supply, Sector Building (Construction), Transport and Communiaztion Sector, Financial Sector Real Estate and Services Company, as well as the servicls sector. Retarded sector that currently exists is the Mining and Quarrying sector.